PENERAPAN STUDENT CENTERED LEARNING PADA POKOK BAHASAN PENULISAN PROPOSAL PKM MATA KULIAH BAHASA INDONESIA MAHASISWA SEMESTER I PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Sujinah (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The problem of this research is how effective is the implementation of SCL approach in the lecture of Students’ Creativity Proposal writing within Bahasa Indonesia subject at Indonesian language and literature study program 2015/2016 academic year. Data collection method to describe the finding of this research were test series (written, product and performance) and questionnaire. From the result of this research, it is it can be concluded that the implementation of SCL in the research setting was very effective. The effectiveness can be seen from the result of data collection through test (written, product, and performance) and from the questionnaire. The data showed that students’ competence in the lecture of Students’ Creativity Proposal writing within Bahasa Indonesia subject was successfully good. By implementing SCL lecturers gained input concerning the mastered aspects and the aspects which have not been mastered by the students. As a result, by using the finding of this research in the later meetings, the lecturer can make some improvement to his/her teaching.